The study of propranolol treatment for hemangioma of infancy- A hospital based observational study - Khatun, Masuda; Sayed, MM Abu; Pervin, Monira (Journal of Paediatric Surgeons of Bangladesh, 2018)
Background: Infantile haemangiomas are the most common tumours of infancy, regularly encountered in dermatology and paediatric practices. Methods: One hundred patients from Dhaka Medical College Hospital were treated with oral propranolol for IHs between May 2015 and December 2015. Results: Majority 25(69.45%) patients belonged to age ≤6 months, the mean age was found 4.2±5.0 months. Males were predominant (80.6%). Male female ratio was 4.14:1. Regarding facial segments 10(27.8%) patients had S3. Two (6.0%) patients had trunk lesions. Eyelid was found 6(17.0%). Ulcerated hemangioma was found in 4(12.0%). Mean severity scores were significantly reduces from 4 to 32 weeks when compare with baseline and different follow up. Conclusion: Majority hemangioma patients belonged to age ≤6 months, mean severity scores were significantly reduced from 4 to 32 weeks when compared with baseline and different follow up. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (1): 11-14